Use of tree rings as a bioindicator to observe atmospheric heavy metal deposition - Turkyilmaz, Aydin; Sevik, Hakan; Isinkaralar, Kaan; Cetin, Mehmet (Springer Science and Business Media LLC, 2019)
Trees can be used as good indicators to evaluate the increase in atmospheric heavy metal concentrations. In the last two decades, air pollution in the city of Ankara has rapidly increased with the ever-increasing traffic density. In the present study, the depositions of aluminum (Al), zinc (Zn), copper (Cu), cobalt (Co), iron (Fe), manganese (Mn), chrome (Cr), cadmium (Cd), sodium (Na), calcium (Ca), barium (Ba), phosphor (P), magnesium (Mg), arsenic (As), and boron (B) in the rings of oak trees were analyzed using a GBC Integra XL-SDS-270 ICP-OES device. The study found that heavy metal concentrations in tree rings varied over the past 20 years; furthermore, there was a significant relationship between the heavy metal concentrations in tree rings and the atmospheric heavy metal concentrations. There was an increase in the concentrations of nutritional elements (Na, P, and Mg) in 2010 when there was excessive precipitation. As a result, the concentrations of all elements in the woods of different ages were significantly different at a confidence interval of 95% for As, 99% for Cd, and 99.9% for other elements.
Keywords: Quercus; Environmental Biomarkers; Turkey; Air Pollution; Metals, Heavy; Cities; Environmental Monitoring; Vehicle Emissions; 13. Climate action; 11. Sustainability; 15. Life on land